Telling stories to understand research impact: narratives from the Lenfest Ocean Program. (3rd October 2022) - Hudson, Charlotte G; Knight, Emily; Close, Sarah L; Landrum, Jason P; Bednarek, Angela; Shouse, Ben
Abstract: For almost 20 years, the Lenfest Ocean Program has funded research projects around the world to generate information that managers, policymakers, and communities can use to develop solutions to ocean and coastal threats. To assess our grantmaking, we wanted to understand whether our philanthropic contribution has had an impact both inside and outside of academic circles. We found that narrative storytelling, as an alternative to a formal analysis, allowed us to explore the different dimensions of research impact, such as how scientific information can prompt progress toward sustainable management or policy change, how a research project's structure can facilitate impact, and how building relationships and trust among project participants throughout a project may increase the use of future research results. Both the process of documenting the activities and events that resulted from funded projects from various perspectives and the writing of the story itself, helped us understand how science was or wasn't used. By sharing what we have learned about projects that successfully informed management decisions as well as projects that fell short of their goals, we hope to shed light on the complex relationship between science and environmental decision-making through the lens of research impact.